Exploration of Energy Metabolism in the Mouse Using Indirect Calorimetry: Measurement of Daily Energy Expenditure (DEE) and Basal Metabolic Rate (BMR). Issue 3 (1st September 2015) - Meyer, Carola W.; Reitmeir, Peter; Tschöp, Matthias H.
Abstract : Current comprehensive mouse metabolic phenotyping involves studying energy balance in cohorts of mice via indirect calorimetry, which determines heat release from changes in respiratory air composition. Here, we describe the measurement of daily energy expenditure (DEE) and basal metabolic rate (BMR) in mice. These well‐defined metabolic descriptors serve as meaningful first‐line read‐outs for metabolic phenotyping and should be reported when exploring energy expenditure in mice. For further guidance, the issue of appropriate sample sizes and the frequency of sampling of metabolic measurements is also discussed. © 2015 by John Wiley & Sons, Inc.